Robust and Reversible Vapoluminescent Organometallic Copper Polymers. Issue 11 (10th May 2018) - Peng, Hao; Xin, Yumeng; Shen, Wei; Deng, Zhengtao; Zhang, Jiuyang
Abstract: Emissive organometallic polymers are an important class of functional materials characterized by the combined photoluminescent features of organometallic molecules and the properties of traditional polymers. In this work, the emissive organometallic complex, [CuBr(PPh3 )2 (4‐methylpyridine)], is successfully, mechanically ground into a random copolymer built on 4‐(diphenylphosphino)styrene (DPVP) and n ‐butyl acrylate (BA) monomers. The resultant hybrid materials successfully inherit the emissive centers, and are significantly reinforced by the copper complexes as chemical crosslinkers in the polymeric continuum. These organometallic polymers are also proved to have excellent vapoluminescent properties, exhibiting unique responses to many organic solvent vapors, reflecting their rapid loss and recovery of photoluminescence. Mechanically robust and flexible films prepared with these organometallic Cu(I)‐polymers are tested as recoverable sensors for hazardous volatile chemical compounds (VOCs) such as toluene, acetone, chloroform, and dichloromethane, and the low limits of detection (LOD) can reach as low as 1 × 10 −3 –8 × 10 −3 mg L −1 (0.2–3.3 ppmV, parts per million‐volume) for various VOCs. This work sheds lights on the design and fabrication of organometallic polymers for advanced applications. Abstract : In this work, a new photoluminescent metallopolymer through the simple grinding of copper(I) salts with triphenylphosphine polymers is reported. These organometallic polymers are also proved to have excellent vapoluminescent properties, exhibiting unique response to many organic solvent vapors, reflecting their rapid loss and recovery of photoluminescence.